Sago starch: behaviour and manufacture of expanded iron-fortified extrudates - Fitriani, Shanti (2016)
Sago starch is extracted from the trunk of sago palm (Metroxylon spp.), which is found throughout South East Asia. In Indonesia sago is considered an underutilised crop and moreover Iron Deficiency Anaemia (IDA) is prevalent among particularly women and children. Creation of a ready to eat product from sago, which was fortified with iron, would address issues of food security both in terms of nutrition and as a non-imported carbohydrate source. With this aim studies for the manufacture of a thermomechanical directly expanded snack product using a commercial source of sago starch were conducted.